Pemberdayaan Karang Taruna Putra Jaya Intan di Bidang Pendidikan, Kewirausahaan, dan Olahraga - Maulana, Maulana; Nugraha, Dadan; Ridwan, Heri (Jurnal Pengabdian Masyarakat PGSD, 2023)
Karang Taruna is an organization formed by the community as a forum for the younger generation to develop themselves, grow, and develop on the basis of awareness and social responsibility of younger generation, which is oriented towards achieving social welfare for the community. Karang Taruna empowerment is a process of developing capabilities, opportunities, and granting authority to Karang Taruna to increase potential, prevent and handle social problems, develop pioneering values through the use of human resources, natural-social resources, and technology. This empowerment is also felt by the Karang Taruna "Putra Intan Jaya" which is domiciled in Langkaplancar District, Pangandaran Regency. In the course of the Karang Taruna there were several obstacles, especially those related to organizational management; human resource capacity (education); capacity of economic resources (entrepreneurship); facilities and infrastructure (education and sports). In practice, empowerment is carried out in the form of improving organizational management, human resource capacity as well as facilities and infrastructure. Organizational management improvement is carried out through guidance and provision of organizational equipment. Capacity building for human resources is carried out through education, training, guidance, and best practice. Then, improvement of facilities and infrastructure is carried out through the provision, addition and development of equipment